HEALTHY AGING: A STUDY IN VIEW OF THE ELDERLY IN PRIMARY CARE (Fiep Bulletin - online, 2012)
Abstract: In the context of several limitations that increasing age may result, be it physical, mental or social activity theory that addresses the functional aspects of individual and involve the modifications related to the anatomical conditions, and psychological health of old age, with however, the persistence of psychological and social needs. This study addressed the issue of social representation of aging from the perspective of the elderly in the Family Health Strategy (FHS). It is a descriptive exploratory study was conducted with seventy elders, who were assisted by the ESF Rangel II, the city of João Pessoa. Data were collected through interview technique and analysis of the data was performed with the help of a software for quantitative analysis of textual data called Alceste. The results show that the social representations of aging are permeated with negative content, however, not associated with the old word 'health' but it is represented as a 'sickness' which shows the difficulties experienced by the subjects of study. It was evident that the feelings of being elderly in Brazil, for the respondents mean an end of life, where age is a sentence: death and oblivion - the latter, if not physical, but social death, a life without quality, into oblivion, with many problems and diseases. This negative view of aging is usually associated with different losses experienced by the elderly, such as: physical, mental, psychological, social and family. Need to change this view biologist for the new paradigm of active aging quality in the elderly have autonomy and independence as it is known that these representations are the result of negative social interpersonal relationships of the elderly in their most intimate spaces, and living experiences of disrespect social exclusion.
Keywords: Aging; Caring; Primary Care.